Chinese Education at Confucius Institutes in Belgium: A Pedagogical and Socio-Cultural Perspective - Meng Song; Lies Sercu (Dutch Journal of Applied Linguistics, 2023)
This poster presents the overview and the first step of the PhD project Chinese Education at Confucius Institutes in Belgium: A Pedagogical and Socio-Cultural Perspective. In recent decades, the enhanced globalization (Badwan, 2021) and mobility (McWilliams, 2008) have increased the complexity in foreign language classrooms in multilingual contexts (Bonnet & Siemund, 2018). It is thus worthwhile to explore the dynamics among diverse pedagogical and socio-cultural factors in real-life practices of foreign language education. Situating this issue in Belgium, this project investigates Chinese as a foreign language (CFL) education at local Confucius Institutes (CIs), aiming to provide insights into educational approaches at CIs as designed; delivered and received by different stakeholders (administrators, teachers, and learners).